2017
DOI: 10.2320/matertrans.m2017115
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Unusual Wetting of a Surface Fine Crevice Structure Created by Laser Irradiation

Abstract: We investigated the detailed mechanism of the unusual wetting of liquid metal bismuth on the surface ne crevice structure of copper metal created with laser-irradiation by focusing on the wetting state during the course of wetting. It was observed that liquid bismuth in ltrates into the ne pore and the interspaces on the surface ne porous structure, and wets on the surface ne crevice structure itself ahead and behind the wetting front, respectively. This revealed that the unusual wetting on the surface of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…5) We posit that super-spread wetting of liquid metal on the surface fine crevice structure derived from capillary action through the three-dimensional connected microcrevice gaps. 4) We consider that the fine surface structure mediates capillary action, that is, wetting behavior; nevertheless, the formation mechanism of the surface fine crevice structures produced by laser irradiation remains poorly understood. To further develop applications of this method, it is necessary to understand the formation mechanism of the fine structure during laser irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…5) We posit that super-spread wetting of liquid metal on the surface fine crevice structure derived from capillary action through the three-dimensional connected microcrevice gaps. 4) We consider that the fine surface structure mediates capillary action, that is, wetting behavior; nevertheless, the formation mechanism of the surface fine crevice structures produced by laser irradiation remains poorly understood. To further develop applications of this method, it is necessary to understand the formation mechanism of the fine structure during laser irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that super-spread wetting proceeds via gradual wetting of microscopic structure to wetting of macroscopic structure on the surface fine crevice structure produced by laser irradiation. 7) It was supposed that the super-spread wetting of the interface fine mesh structure in this study occurs by a similar mechanism to that of the surface fine crevice structure. The gap size of interface fine mesh structure in Fig.…”
Section: Resultsmentioning
confidence: 62%
“…Our research group [13][14][15] originally found that super-spread wetting occurs on the surface fine porous structure that is produced by atmospheric oxidation-reduction treatment of a metal surface. In further studies, we found two kinds of surface fine crevice structures that can promote region-selective super-spread wetting of liquid metals: namely, (1) a laser-irradiated surface fine crevice structure, created by laser irradiation [16][17][18][19][20] and (2) a powder-based surface fine crevice structure, created by reduction sintering of an oxide powder [21] on copper and iron surfaces. Super-spread wetting of these two surface fine crevice structures showed that similar and dissimilar metal-to-metal joining, such as Cu-Cu [16,17,21] and Cu-Fe [20] joining, can be achieved.…”
Section: Introductionmentioning
confidence: 97%
“…Our research group discovered a phenomenon known as "super-spread wetting", in which a liquid metal penetrates into the fine surface structure of a solid metal that has high porosity, similar to that of a sponge structure, by capillary action, and completely spreads on that surface [13][14][15][16][17][18][19][20][21]. Our research group [13][14][15] originally found that super-spread wetting occurs on the surface fine porous structure that is produced by atmospheric oxidation-reduction treatment of a metal surface.…”
Section: Introductionmentioning
confidence: 99%